Strength Analysis of S275 JOH Material Using Charpy Impact Test Equipment - M. Tri Maulady Alamsyah; Wilarso (Universitas Medan Area, 2025)
S275 JOH is a structural steel widely used in the construction of bridges, buildings, and other infrastructure. This study aims to evaluate the material's impact strength through Charpy impact testing on two types of specimens: SHS (Square Hollow Section) and RHS (Rectangular Hollow Section). Testing was conducted at 10°C according to the EN 10210-1 standard. The results show that the 75x75 mm SHS has an average impact energy value of 105.90 J, higher than the 100x200 mm RHS with a value of 78.79 J. Despite a decrease of approximately 25% in RHS, both specimens still meet the minimum requirement of 27 J according to the standard. This study provides a scientific basis for selecting structural steel materials based on impact strength.